The Effect of Inventory Turnover Ratio and Total Asset Turnover Ratio on Profitability Economics at PT. Alfa Scorpii Sibolga - Febri Syahraini Nasution; Safriadi Pohan; Rahmadiah Hanum (Jurnal Stagflasi : Ekonomi, Manajemen dan Akuntansi, 2024)
The objective of this study is to ascertain whether PT. Alfa Scorpii Sibolga's economic profitability is significantly impacted, partially and concurrently, by the inventory turnover ratio (X1) and total asset turnover ratio (X2). Multiple linear regression analysis, hypothesis testing, and classical assumption testing are the data analytic techniques used. By gathering PT financial reports, secondary data was obtained for this study. Alfa Scorpii Sibolga, comprising a profit and loss statement and balance sheet for the years 2018 through 2022. The balance sheet and profit and loss report of PT. Alfa Scorpii Sibolga for the years 2018 through 2022 served as the research sample. The inventory turnover ratio and total asset turnover ratio both had an insignificant impact on economic profitability concurrently, according to the F test results, which had a F value of 0.390 at a significance level of 0.719. The results of the partial t test demonstrate the degree of significance that was determined by the independent variables, which are the total asset turnover ratio (0.874) and the inventory turnover ratio (-0.823). This demonstrates that the total asset turnover ratio has a negligible positive impact on economic profitability and the inventory turnover ratio has an insignificant negative impact. Based on the study's findings, the researcher recommends that before making an investment, investors consider the value of the inventory turnover ratio and total asset turnover ratio. Additionally, businesses should focus on inventory and total asset management by analysing the inventory turnover ratio and total asset turnover ratio to increase productivity and profitability.